The abundance of nematode in cabbages grown in conventional and organic farming systems / Hendry Joseph and Sharmiza Sinin - Hendry Joseph; Sharmiza Sinin (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
A study on the abundance of nematodes in cabbages grown in two different farming systems was carried out in Kundasang, Sabah. The aim was to compare the population of nematodes in organic and conventional farming systems. Soil samples were collected in September 2013 during the cabbage growing season. Nematodes were extracted from soil using Baermann funnel method. The results revealed that conventional farming favoured the population of plant feeder nematodes, whereas the organic farm had significantly higher population of total free living nematodes during the period of the study. However, the negative correlation in population of plant feeder and free living nematodes indicated that there was no competition between the two nematode populations in the soil.